Capsaicin for neuropathic pain: linking traditional medicine and molecular biology - Haanpää, Maija; Treede, Rolf-Detlef (European neurology, 2012)
Capsaicin has long been used as a traditional medicine to treat pain and, recently, its mechanism of analgesic action has been discovered. This review article documents the clinical development of capsaicin to demonstrate that pharmacognosy still has a profound influence on modern-day drug development programs. Capsaicin is a highly selective agonist for the transient receptor potential channel vanilloid-receptor type 1 (TRPV1), which is expressed on central and peripheral terminals of nociceptive primary sensory neurons. Knockout studies have revealed the importance of TRPV1 as a molecular pain integrator and target for novel analgesic agents. Topical application of capsaicin at the peripheral terminal of TRPV1-expressing neurons superficially denervates the epidermis in humans in a highly selective manner and results in hypoalgesia. In three recent randomized controlled trials, a patch containing high-concentration capsaicin demonstrated meaningful efficacy and tolerability relative to a low-concentration capsaicin control patch in patients with peripheral neuropathic pain. Data from clinical practice will determine if the high-concentration capsaicin patch is effective in real-world settings.